(untitled) (Journal of Ideas in Health, 2020)
The new type of Coronavirus (SARS-CoV-2) is a highly contagious pathogen that causes severe acute respiratory syndrome and can be transmitted from human to human. COVID-19, which has been declared as a pandemic by the world health organization and is infected with more than 50 million people, is also responsible for the death of more than 1 million people. There is no sufficient data from randomized clinical trials that any potential treatment improves outcomes in COVID-19 patients. Chloroquine and hydroxychloroquine, antivirals such as favipiravir, lopinavir/ritonavir, immunomodulatory agents tocilizumab, siltuximab, and sarilumab, and anti-inflammatory drugs such as steroids are used for the treatment of COVID-19. Repurposing drugs can provide new treatment options faster than discovering new drugs due to the known safety profiles of existing drugs. On the other hand, there are new drug and vaccine trials for COVID-19. Many researchers, governmental or non-governmental institutions having clinical trials for COVID-19 drugs and vaccines. In this comprehensive review, we investigate the clinical features, management, and treatment of COVID-19 and possible adverse effects and important information related to drugs used for COVID-19. For future preparedness and readiness, new laws and legislations should be constituted. Besides, emergency teams and budgets should be prepared as well. .